Analytical Model for the Performance Curves of a Family of Propellers based on Wind Tunnel Tests - Santos, Miguel Cabeleira dos (2020)
Made available in DSpace on 2020-01-16T16:46:15Z (GMT). No. of bitstreams: 1 6552_14392.pdf: 9374726 bytes, checksum: 36178ca2edf0bbee581140fb0a569ada (MD5) Previous issue date: 2018-12-04